Subjective Hesitation in Paul Auster’s Report from the Interior: ‘you think of yourself as anyone, as everyone’ - Nicolas Pierre BOILEAU (E-REA)
Report from the Interior, Auster’s 2013 memoir opens with the earliest memories of young Paul up to the age of 12 before the author looks at tokens of his past in three subsequent sections: films, letters and diary entries are reviewed, followed by a final section composed of non-personal photographs. The fragmented structure suggests that the retrospective narrative, which comes, first needs to complement the author’s memory. These objects also seem to supplement language where it fails to be referential. Paul Auster’s latest memoir surprisingly suggests the pre-existing knowledge of how a child’s ‘interior’ develops and a willingness for his own childhood to fit into a larger picture, turning his own life into a mere example of the development of any American-Jewish boy. But for Lacanian psychoanalysis, what is said matters less than the way what remains unsaid still manages to be conveyed and to influence the subject: a reading in these terms enables one to detach oneself from this carefully crafted example of logical reconstruction of subjectivity, and to observe the stitches of open wounds that fail to be entirely cured. The memoir by Paul Auster hinges around a certain understanding of division that is overwhelmingly present in the construction of the text but which, Auster himself admits, does not explain all the forms of division. Through a Lacanian reading, I will try and show what division remains unexplored–the division caused by language–and how this division can be understood in relation to the use of ‘you’ instead of ‘I’ in the text.